Chakde! India - Chopra, Aditya; Amin, Shimit (India : Yash Raj Films International Ltd., 2007)
The story of a coach's fight of making his team, Team India by overcoming their diverse backgrounds, by learning to use everything that life hurls on them as a secret weapon. It's a story about honesty, sincerity and integrity. A story to remind the nation of its national sports
Title from container
Cast : Shahrukh Khan, Vidya Malvade, Anjan Srivastava
VCD format
Malay and English subtitles
Keywords: Hockey -- Drama; Women hockey players -- Drama; Hockey coaches -- Drama